Aplicação da enzima transglutaminase em derivado lácteo com o uso de soro de leite - Sáfadi, Juliana Soares (2019)
This dissertation proposes the application in different concentrations of the transglutaminase enzyme applied to the production process of the fermented dairy product with the use of whey. Annually tons of whey are wasted by the dairy industry and this product is directed to inefficient systems, contaminating the environment. In addition to the environmental issues, the discard of whey is a waste of protein and other nutrients. Based on this, the present work aims the application in different concentrations of the transglutaminase enzyme applied to the production process of the fermented dairy product with the use of whey. It is know that the use of the enzyme represents great potential for the food industry because it allows the protein alteration of several group of foods, manly the dairy fermented products. Therefore, the study methodology was composed by the application of different concentrations of the enzyme, with 0.13%; 0.26% and 0.39% in 700 mL of milk and 300 mL of whey in addition to milk yeast. This process will result in different samples witch will be evaluated by the amount of protein, of viscosity by rheological analysis, thermic stability and biological oxygen demand. Thus, the results showed a significant improvement in protein content, with samples containing around 12% protein, ie 3.9% more than the control group; 58% reduction in BOD indices, increase in viscosity degree and comparing the enzymatic assays to the control group, it can be said that the viability of application is directly related to the use of an important environmental liability, besides the results already presented.